DAMPAK NEGATIVE WALIMATUL 'URS BERLEBIHAN TERHADAP KESTABILAN NAFKAH KELUARGA: ANALISIS HUKUM ISLAM DAN SOSIAL - Jeni Elkana; Yoga Purnama (USRAH: Jurnal Hukum Keluarga Islam, 2026)
The main objective of this research is to analyze the negative impact of excessive walimah celebrations on the fulfillment of family livelihood (nafkah) from the perspective of Islamic law. This study utilizes qualitative field methods employing interviews and documentation, and its analysis is conducted using a descriptive-analytical approach. The findings reveal that extravagant walimah creates long-term debt burdens, disrupts the fulfillment of primary needs, limits secondary necessities, and may lead to emotional pressures within the household. Although society often views elaborate walimah positively, in practice such conduct contradicts the principle of simplicity, la dharar wa la dhirar, as well as the obligation to provide livelihood as stipulated in Article 80 paragraph (4) of the Compilation of Islamic Law. Therefore, walimah should be held in accordance with the family’s financial capacity so that it remains a medium for gratitude and social bonding without sacrificing family welfare.